PEREMPUAN DALAM JERATAN EKSPLOITASI MEDIA MASSA - Syafrini, Delmira (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2014)
Exploitation of women now comes in new faces; through the mass media. Media currently has a dual role, like two sides of a coin, on one side the media serves as a mediator for the improvement and progress of the nation, on the other side contributes to the suppression of media for the benefit of market capitalism toward consumer culture women once again being the subject of image construction. Expansion of the market and the mass media can not be separated from the flow of consumerism, because the mass media (particularly advertising on television) is an extension of the market to boost sales of industrial products in the form of imagery that originates from the